Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Front row: Albert Watkins, Madelyn Watkins Lange, Jessica Barry Watkins Shoemaker and Ann Watkins Thompson; Back row: Pauline Shoemaker Gibson, Bernice Shoemaker Blackburn, Violet Swaggerty Goins, Ethel Swaggerty Wooden, Jacklyn Watkins Adams and Francis Watkins Goins